Pengaruh Work Life Balance Terhadap Kepuasan Kerja Pada Karyawan Outsourcing PT. X - Maully Dina, Lady; Aulia, Lailatuzzahro Al-Akhda (Psychopreneur Journal, 2024)
This study aims to determine and measure the effect of work life balance on job satisfaction of outsourced employees at PT. X. This research uses quantitative methods. The subjects of this research were 143 employees. Data collection uses a job satisfaction scale and a work life balance scale. Analysis of this research data used exponential non-linear regression analysis, and the calculated F value was 7.055, which was greater than the F table, namely 3.91. So there is an influence between the work life balance variable (X) on the job satisfaction variable (Y). It is known that the R value, namely 0.218, is in the low category, but shows a positive correlation between the criterion (Y) and the predictor (X). From the calculation results, it is known that the R square value is 0.048, which means that work life balance has an influence of 4.8% on the job satisfaction of PT outsourcing employees. X. This value means that work life balance (X) can affect 4.8% in job satisfaction (Y) while 95.2% is influenced by other factors or variables that are not examined in this study.